Effect of national HIV testing recommendations and local interventions on HIV testing practices in a Swiss university hospital: a retrospective analysis between 2012 and 2015. Issue 10 (3rd October 2018) - Lazzarino, Tosca; Martenet, Sebastien; Mamin, Rachel; Du Pasquier, Renaud A; Peters, Solange; Perreau, Matthieu; Muller, Olivier; Hugli, Olivier; Cavassini, Matthias; Darling, Katharine Elizabeth Anna
Abstract : Objectives: Despite HIV testing recommendations published by the Federal Office of Public Health (FOPH) since 2007, many individuals living with HIV are diagnosed late in Switzerland. The aim of this study is to examine the effect of the 2013 FOPH HIV testing recommendations on HIV testing rates. Setting: Ten clinical services at Lausanne University Hospital, Lausanne, Switzerland. Participants: Patients attending between 1 January 2012 and 31 December 2015. Design: Retrospective analysis using two existing hospital databases. HIV testing rates calculated as the percentage of tests performed (from the Immunology Service database) per number of patients seen (from the central hospital database). Primary and secondary outcome measures: The primary outcome was testing rate change following the 2013 FOPH testing recommendations, comparing testing rates 2 years before and 2 years after their publication. Secondary outcomes were demographic factors of patients tested or not tested for HIV. Results: 147 884 patients were seen during the study period of whom 9653 (6.5%) were tested for HIV, with 34 new HIV diagnoses. Mean testing rate increased from 5.6% to 7.8% after the recommendations (p=0.001). Testing rate increases were most marked in services involved in clinical trials on HIV testing, whose staff had attended training seminars on testing indications and practice. Testing rates were lower among older (aged >50 years), female and Swiss patients compared with younger, male and non-Swiss patients, both globally (p=0.001) and in specific clinical services. Conclusions: This simple two-database tool demonstrates clinical services in which HIV testing practice can be optimised. Improved testing rates in services involved in clinical trials on testing suggest that local engagement complements the effect of national recommendations. While, overall, HIV testing rates increased significantly over time, testing rates were lower among patients with similar demographic profiles to individuals diagnosed late in Switzerland.